Influence of Green Brand Knowledge and Positioning on Perceived Value and Purchase Intention among Le Minerale Consumers in Semarang City - Zahrotul Lailatus Saadah; Asyhari Asyhari (Komunitas Dosen Indonesia, 2026)
This research focuses on examining how Green Brand Knowledge and Green Brand Positioning impact Perceived Value and, in turn, affect Purchase Intention for Le Minerale products in Semarang City. A quantitative method is employed, utilizing explanatory research. The target group includes consumers of Le Minerale in Semarang City, selected through a purposive sampling method, comprising between 100 to 150 participants. Data collection involved a questionnaire using a Likert scale, which was analyzed via Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The findings reveal that Green Brand Knowledge significantly and positively influences both Perceived Value and Purchase Intention. Additionally, Perceived Value positively and significantly impacts Purchase Intention. However, Green Brand Positioning does not exert a significant direct effect on Purchase Intention but does positively and significantly affect Perceived Value. These results suggest that Perceived Value serves as an intermediary factor in enhancing Purchase Intention for Le Minerale products in Semarang City.